Association of autoantibodies against the M2-muscarinic receptor with long-term outcomes in peripartum cardiomyopathy patients: A 5-year prospective study. Issue 3 (September 2019) - Ma, Guiling; Wang, Yidan; Hou, Dongyan; Liu, Jiamei; Zhang, Juan; Xu, Lin; Wang, Hua; Zhao, Wenshu; Zhang, Yuan; Zhang, Lin
Highlights: Increased serum anti-M2-muscarinic receptor (anti-M2-R) in peripartum cardiomyopathy (PPCM) patients. Being positive for anti-M2-R is an independent risk factor for the onset of PPCM. PPCM patients have better prognosis especially in anti-M2-R (−) patients. Abstract: Background: Peripartum cardiomyopathy (PPCM) is characterized by heart failure. Our previous study found that autoantibodies against the M2-muscarinic receptor (anti-M2-R) are increased in PPCM patients. We aimed to evaluate the association of anti-M2-R on prognosis of PPCM patients with standard treatment. Methods: Synthetic peptides corresponding to the M2 receptor served as the target antigens in an enzyme-linked immunosorbent assay experiment. They were used to screen the sera of 80 PPCM patients, who were separated into anti-M2-R-negative and positive groups according to their anti-M2-R reactivity. Clinical assessment and echocardiography examination were performed at baseline and after 5 years with a standard treatment regimen. The endpoint events were compared after 5 years of follow-up. Results: There were 76 PPCM patients who completed the final data analysis, including 36 in the anti-M2-R (+) group and 40 in the anti-M2-R (−) group. Both groups showed improvement in the left ventricular end-diastolic and end-systolic dimensions and the ejection fraction with standard treatment regimens for 5 years (all p < 0.001). Patients in the anti-M2-R (−) group had greater tolerance and were more rapidly titrated to metoprolol, and they had better improvement in cardiac function than patients in the anti-M2-R (+) group ( p < 0.05). Patients in the anti-M2-R (−) group had a marked decrease in re-hospitalization ( p < 0.05), but not in all-cause mortality or cardiovascular mortality. Being positive for anti-M2-R increased the risk of PPCM (OR = 4.7, 95% CI 1.8–12.2, p = 0.002). Conclusions: PPCM patients, especially anti-M2-R (−) patients, have a relatively better prognosis than other patients. We posit that the presence of anti-M2-R may be involved in the pathogenesis of PPCM.